Zero-Disturbance Control of Free-Floating Space Manipulators Using Integral-Type Sliding Mode Control. (27th May 2015) - Li, Heping; Li, Ren
Abstract : A free-floating space manipulator is an underactuated system, of which the spacecraft is permitted to rotate freely in response to the manipulator motions. The dynamic coupling property between the spacecraft and the manipulator makes motion control of such systems a significant challenge. In the paper, a zero-disturbance control method for free-floating space manipulators operating in task space is presented. An explicit direct relationship between the spacecraft attitude quaternions and the manipulator joint variables is established using nonholonomic constraints of the angular momentum conservation. By this means the kinematic redundancy of the system is used to adjust the spacecraft attitude. An integral-type sliding mode controller with adaptive switching gains is developed for coordinated motion control of the spacecraft and the manipulator. Simulations on three-link planar model show that the spacecraft remains undisturbed during the whole process of manipulations, which confirms the effectiveness of the proposed method.